Mutational Analysis of the Human Immunodeficiency Virus Type 1 Vif Protein - Simon, James H. M. (American Society for Microbiology, 1999)
Lentivirus Vif proteins are potent regulators of virus infectivity. However, relatively little is known about the functional domains, peptide motifs, or residues of any Vif protein. In this report, we present the first extensive mutagenesis analysis of the 192-amino-acid human immunodeficiency virus type 1 (HIV-1) Vif protein. A large number of scanning missense (mostly alanine substitution) and deletion mutations were introduced into the HIV-1(HXB3) vif gene, and the resulting proteins were evaluated for the induction of virus infectivity as well as subcellular localization. The results show that amino acids dispersed throughout Vif’s linear sequence are important for function. However, because many of the inactive proteins also appear to be mislocalized, we suggest that many of them may actually be misfolded rather lacking an intracellular targeting signal. Interestingly, disruptions within an internal region spanning residues 114 to 146 give rise to mutant proteins that either retain function or are inactive but are not substantially mislocalized. We therefore speculate that this region, which harbors two essential cysteine residues and one essential serine residue, may contain aspects of a putative Vif effector domain.